Hydrogel Coils versus Bare Platinum Coils for the Treatment of Ruptured and Unruptured Aneurysms: An Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials - Cortese, Jonathan; Ghozy, Sherief; Zarrintan, Armin; Bektas, Delal; Al-Janabi, Omar M; Verma, Onam; Bayraktar, Esref Alperen; Brinjikji, Waleed; Kadirvel, Ramanathan; Kallmes, David F (American journal of neuroradiology : AJNR, 2025)
Whether hydrogel coils (HGCs) can reduce intracranial aneurysm recurrences when compared with bare platinum coils (BPCs) remains a disputed subject. Thus, we sought to perform a systematic review and meta-analysis to evaluate the efficacy of hydrogel coils in the context of intracranial aneurysm treatment. Following PRISMA 2020 guidelines, we systematically reviewed PubMed, Scopus, Embase, and Web of Science for randomized controlled trials (RCTs) comparing HGC to BPC. Outcomes of interest were: end of procedure and last follow-up occlusion rates, including complete occlusion and major recurrence, complication rates, morbidity, and mortality. Risk ratios (RRs) and 95% CIs were calculated. The study selection: 5 RCTs, including 2126 patients (HGC = 1064, BPC = 1062), were analyzed. HGC showed comparable rates of immediate complete occlusion (RR = 0.89, 95% CI = 0.68-1.16, = .29) and packing attenuation (MD = 27.17, 95% CI = -16.59-70.93, = .12) compared with BPC. At an average 18-month follow-up, HGC significantly reduced major recurrence rates (RR = 0.75, 95% CI = 0.60-0.94, = .03). Complete occlusion rates at the last follow-up were higher for HGC after outlier exclusion (RR = 1.29, 95% CI = 1.18-1.42, < .001). All the outcomes related to complications, including hemorrhagic and thromboembolic complications, were similar between both groups ( > .1 for all). Finally, HGC resulted in similar rates of mRS 0-2 and mortality compared with BPC (RR = 0.98, 95% CI = 0.95-1.01, = .15 and RR = 0.72, 95% CI = 0.31-1.65, = .33, respectively). Only 5 RCTs were included in this meta-analysis, which may limit the generalizability of our findings. The absence of long-term follow-up also limits the assessment of treatment durability. Our meta-analysis of RCTs suggests that the use of HGC in the endovascular treatment of intracranial aneurysms results in significantly lower rates of recurrence compared with BPC, with both coil types showing similar initial occlusion rates and safety profiles.